MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI POKOK SIMETRI LIPAT MELALUI MODEL KOOPERATIF TIPE PROBING PROMPTING - Mariyatun, Mariyatun (Vidya Karya Jurnal Kependidikan, 2013)
Classroom action research (CAR) aims to improve mathematics learning outcomes of of 5th grade students of SDN 2 Pembataan in fold symmetry material. On academic year 2011/2012 . Classroom action research carried out in two cycles, and each cycle implemented at three times of learning, where each meeting consists of a 2 hour lesson. The data include student understanding measured using test instruments, process skills measured using observation sheets, student responses measured using a questionnaire, and learning activities measured using observation sheet. Furthermore, the data were analyzed descriptively. Students declared complete when student learning outcomes at 6.5 based on Minimal Mastery Learning Criteria (KKM). Classical completeness is achieved if 80 % of students achieving KKM. The research showed that the implementation of cooperative learning model of probing prompting type in the subject matter of fold symmetry on a flat form in SDN Pembataan improves studentsâ mastery learning from first cycle to the second cycle, both individual and classical.